2000
DOI: 10.1128/aem.66.1.352-358.2000
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Rearrangements of the Regions Adjacent to Genes Encoding Heat-Labile Enterotoxins ( eltAB ) of Enterotoxigenic Escherichia coli Strains

Abstract: One of the most common bacterially mediated diarrheal infections is caused by enterotoxigenic Escherichia coli (ETEC) strains. ETEC-derived plasmids are responsible for the distribution of the genes encoding the main toxins, namely, the heat-labile and heat-stable enterotoxins. The origins and transfer modes (intra-or interplasmid) of the toxin-encoding genes have not been characterized in detail. In this study, we investigated the DNA regions located near the heat-labile enterotoxin-encoding genes (eltAB) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 48 publications
0
31
0
Order By: Relevance
“…A previous report indicated that around 130 million years ago, before V. cholerae and E. coli diverged as species, LT genes were acquired by horizontal transfer (40). Also, it has been known that the LT sequence is flanked by insertion sequence (IS) elements, similar to those found next to genes encoding fimbriae, suggesting a general mechanism for the transmission of virulence-related genes (41,42). Our data, together with the findings that ETEC strains with the same toxin-CF profile often are genetically related, suggest that LT acquisition is not due solely to horizontal gene transfer but rather is also due to lateral gene transfer.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report indicated that around 130 million years ago, before V. cholerae and E. coli diverged as species, LT genes were acquired by horizontal transfer (40). Also, it has been known that the LT sequence is flanked by insertion sequence (IS) elements, similar to those found next to genes encoding fimbriae, suggesting a general mechanism for the transmission of virulence-related genes (41,42). Our data, together with the findings that ETEC strains with the same toxin-CF profile often are genetically related, suggest that LT acquisition is not due solely to horizontal gene transfer but rather is also due to lateral gene transfer.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is likely that CRP acts at an earlier step of promoter initiation by sterically occluding RNA polymerase's access to the Ϫ35 hexamer of eltAp. Although ETEC strains are heterogeneous, it is likely that LT-I will be negatively regulated by CRP in most, if not all, LT-I ϩ strains because the CRP binding site centered at Ϫ31.5 is a conserved feature of the toxin promoter (39).…”
Section: Discussionmentioning
confidence: 99%
“…IS91 or very closely related isoforms have also been found adjacent to various other virulence genes in enteropathogenic, enterohemolytic, and enterotoxigenic strains of E. coli (16,42,109), including the eltAB toxin-encoding genes of the heat-labile enterotoxin (89). Furthermore, direct movement of eltAB genes by IS91 has been demonstrated (89). Similarly, IS1294 has been associated with virulence genes in E. coli (96), and IS801 has been discovered in close association with virulence genes in the plant pathogen Pseudomonas syringae (66,83,95).…”
Section: Is91 and Virulence Factorsmentioning
confidence: 99%
“…For example, in Argentina, the bla CTX-M-2 enzyme alone now accounts for almost 69% of all ESBLs in Enterobacteriaceae that are analyzed in Buenos Aires (30). In both instances, the resistance genes are closely associated with ISCR1 (13,89).…”
Section: Iscr1mentioning
confidence: 99%
See 1 more Smart Citation